EFEKTIVITAS PENERAPAN MODEL KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENT) TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL KELAS IV MADRASAH IBTIDAIYAH MA'HAD AL-ZAYTUN - Ghina Aribah, Amara; Iswandi, Irvan; Utami, Dewi (Cahaya Ilmu Bangsa Institute, 2024)
This research was conducted because, in Social Science learning, the teaching methods used are still limited to lectures and assignments, which tend to be monotonous. This monotonous learning approach leads to a lack of active involvement of students in the teaching and learning process so students are not interested in the material presented which have an impact on their learning outcomes. To overcome this problem, researchers tried to make improvements by applying the Team Games Tournament type cooperative learning model in Social Science learning. The purpose of this study was to determine the effectiveness of the application of the Team Games Tournament model in social studies learning for grade IV students. This study used a quantitative approach with a Pre-Experiment design with a Group Pretest-Posttest model. Data collection was carried out through learning outcomes tests and questionnaires. The subjects of the study consisted of 20 grade IV students of Madrasah Ibtidaiyah Ma'had Al-Zaytun. Data analysis was carried out using descriptive analysis and inferential analysis, with hypothesis testing in the form of a Paired Sample T-Test. The results showed that there was a significant difference between the average score on the pretest and posttest. On the pretest, the average score of students was in the very low category, which was 42.25 with a standard deviation of 19.566. However, in the posttest, there was a significant increase, with the average score of students reaching the high category, which is 79.25 with a standard deviation of 12.698. In addition, there was an increase in the number of students who achieved minimum completeness scores (KKM) from pretest to posttest, from 2 students to 13 students. The results of the hypothesis test showed that there was a significant difference between the average scores before and after the application of the team games tournament learning model. In addition, the results of the questionnaire also showed a positive and enthusiastic response of students to the application of the learning model. Based on these findings, it can be concluded that the application of the team games tournament learning model is effective and can be applied in class IV MI Ma'had Al-Zaytun in learning Social Sciences. Key Words: Model Team Games Tournament, Learning Outcomes, Social Sciences